Perancangan Sistem Informasi Pendaftaran Online Di Klinik Pratama Bhakti Asih Berbasis Website Dengan Metode Waterfall - Raziq, Akmal; Hasanah, Anifatun; Permatasari, Ayu; Setiawan, Wira (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The development of information technology in the digital era has had a significant impact on various sectors, including healthcare. One notable advancement is the implementation of web-based information systems, which facilitate efficient and organized access to data and information. Klinik Pratama Bhakti Asih in Tangerang City, as a healthcare provider, still relies on manual systems for patient registration and queue management, which hampers efficiency and increases waiting times. This research aims to design and implement an online registration information system based on the Waterfall method to enhance service quality. The system enables patients to register, view doctor schedules, and obtain queue numbers online without having to visit the clinic. Using a qualitative approach and case study, data were collected through observations and interviews with clinic staff and patients. It is expected that the implementation of this system will reduce patient waiting times, speed up administrative processes, and improve the management of patient data at Klinik Pratama Bhakti Asih.